Síntese e caracterização de titanatos lamelares impregnados com Mg2+/MgO ou La3+/La2O3 e sua utilização em reações de transesterificação - Santos, Regiane Lopes dos (2010)
Potassium tetratitanate (K2Ti4O9) and sodium trititanate (Na2Ti3O7) were synthesized by solid state reaction at 800°C and wet impregnated using Mg2+/La3+ or nanoparticles of MgO/La2O3 varying ion/oxide content in 1, 5 or 10% of matrix weight. MgO and La2O3 synthesized by precipitation method and their mean crystallite size calculated in 11 nm and 72 nm, respectively. Synthesized materials were characterized by X ray diffractometry, termogravimetry, N2 adsorption, mid-infrared spectroscopy, transmission electron microscopy and they were applied on transesterification reactions using mixtures of methyl acetate/ethanol and ethyl acetate/methanol. Interlayer distance calculated for solids is about 8 Å. Impregnation of ion/oxide in matrices K2Ti4O9 and Na2Ti3O7 produced structural changes like loss of crystallinity for some of them including peak broadening or disappearing. All synthesized materials, after burning in an atmosphere of N2 (g), lost mass related to the exit of surface water and interlamellar water. Materials showed low surface area, with values below 5 m2/g. In general, powder utilized had conversion rates between 10 and 80%. Emphasis should be given to pure matrices which presented conversions rates equal or higher than impregnated powders, and the use of matrix K2Ti4O9 led to better results. Among the oxides chosen for impregnation, higher efficiency was observed for MgO. Some powders were reused for the same reactions and its activity decreased in each reaction cycle. Reaction mixture analysis after reuse tests to K2Ti4O9 revealed partial leaching of K+ ions, however XRD patterns profile analysis did not show structural changes occurrence. A proposal to explain layered titanate activity on transesterification reactions is made based on acid-base properties of layers and output of K+ from interlamellar area.